2013
DOI: 10.1002/iub.1202
|View full text |Cite
|
Sign up to set email alerts
|

HPIP is upregulated in liver cancer and promotes hepatoma cell proliferation via activation of G2/M transition

Abstract: Hematopoietic pre-B-cell leukemia transcription factor (PBX)-interacting protein (HPIP) has been shown to play a role in cancer development and progression. However, the detailed role of HPIP in cancer cell growth and the exact mechanism by which HPIP regulates cancer cell proliferation remains unclear. Here, we report that HPIP is overexpressed in most of 328 liver cancer patients and regulates hepatoma cell proliferation through G2=M checkpoint activation. HPIP increased anchorage-dependent and -independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…It regulates hepatoma cell proliferation through G 2 /M cell cycle activation and enhances anchorage‐dependent and ‐independent growth of human liver cancer cells. Overexpression of HPIP increases hepatoma cell proliferation, migration, and invasion, and promotes EMT through regulation of mTOR signaling . Similar to upregulation of HPIP expression in breast and liver cancer patients, upregulation of HPIP expression has also been reported in glioma and oral squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It regulates hepatoma cell proliferation through G 2 /M cell cycle activation and enhances anchorage‐dependent and ‐independent growth of human liver cancer cells. Overexpression of HPIP increases hepatoma cell proliferation, migration, and invasion, and promotes EMT through regulation of mTOR signaling . Similar to upregulation of HPIP expression in breast and liver cancer patients, upregulation of HPIP expression has also been reported in glioma and oral squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 80%
“…It is overexpressed in breast infiltrative ductal carcinoma, astrocytoma, and oral squamous cell carcinoma, and promotes cancer cell proliferation, adhesion, and migration . Our recent studies showed that HPIP is overexpressed in liver cancer and promotes hepatoma cell proliferation through activation of G 2 /M cell cycle transition . However, the role of HPIP in gastric cancer is unclear.…”
mentioning
confidence: 99%
“…Recently, accumulating evidence has revealed that HPIP functions as a promoter of the development and progression of cancers, including breast cancer, 2, 3 astrocytoma, 4 liver cancer, 5, 6 oral cell carcinoma, 7 colorectal cancer 8 and so on. However, the role of HPIP in RCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking of HPIP expression can significantly inhibit cell anchorage-dependent and proliferation of human hepatic carcinoma cell 11. Wang et al6 demonstrated that knockdown of HPIP could inhibit thyroid carcinoma cell proliferation, migration/invasion, and epithelial–mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic pre-B cell leukemia transcription factor (PBX)-interacting protein (HPIP) is a novel oncogene that is overexpressed in various human cancers, such as non-small-cell lung cancer,4 human spinal glioblastoma,5 thyroid cancer,6 gastric cancer,7 colorectal cancer,8 breast infiltrative ductal carcinoma,9 oral carcinogenesis,10 liver cancer,11 and human melanoma cell 12. Recent studies have demonstrated the multifaceted role of HPIP in pathways associated with cancer progression, including transformation, apoptosis, invasion, and metastasis 4,6,13,14.…”
Section: Introductionmentioning
confidence: 99%